The Conductivity Enhancement of 1.5Li2O-P2O5 Solid Electrolytes by Montmorillonite Addition - Yustinus Purwamargapratala; Anne Zulfia Syahrial; Teguh Yulius Surya Panca Putra; Evvy Kartini; Heri Jodi (International Journal of Renewable Energy Development, 2023)
Most solid electrolyte materials have not shown enough conductivity to be used as an electrolyte for a battery in electronic devices. The mixture of 1.5 Li2O and P2O5 has been reported to show a good conductivity higher than that of Li3PO4, which is thought to be due to phase mixtures that are formed during manufacturing process. Montmorillonite (MMT) was used to explore the effect of phase mixture on conductivity of new 1.5Li2O-P2O5-MMT solid electrolyte composite, which was prepared through conventional solid-state reaction procedures. This study was conducted, how the addition of MMT affects process of forming 1.5Li2O-P2O5-MMT compound, and whether it influences electrical properties and permittivity of compound. Morphology, hygroscopicity, and electrochemical characteristics of this material were analyzed in this study. The shape of glassy-like flakes was reduced in micrographs, and granular lumps were getting larger as MMT was added. Addition also tended to reduce hygroscopicity, as indicated by a reduced rate of porous absorption. Whole Nyquist plot consisted of only one imperfect semicircular arc, indicating only one relaxation process occurred in materials. Capacitance of all arcs indicated main contribution of response was from bulk material. Slope of dielectric loss of samples indicated that conduction in the samples was mainly dominated by dc conduction. MMT clays acted as a medium that absorbed liquid phase in solid-state reaction, increasing formation of dominant phase, which determined total conductivity of compound. Conductivity was higher than that of Li4P2O7, where the sample of 20 wt% MMT addition was most polarizable and most dielectric compound.